Perfil força-velocidade em jovens futebolistas - Arthur Pereira Ventura (2024)
The present dissertation aimed to analyze the force-velocity (f-v) profile of young soccer players and compare performance variables between different positions and competitive levels. A total of 38 male soccer players (age 17.08 ± 0.94 years; weight 69.08 ± 7.02 kg; height 1.77 ± 0.06 meters) from a team registered with the Portuguese Football Federation participated in the study. Participants performed countermovement jumps (CMJ) with multiple loads related to their body mass, to identify their actual and ideal force-velocity profile (i.e., F0, V0, Sfv, Sfvopt, FVimb, and Pmax). The overall results based on the force-velocity spectrum parameters showed that, of all the subjects analyzed, 26% present a high force deficit, 50% present a low force deficit, 3% present a low velocity deficit and 21% present a well-balanced f-v relationship. Regarding the comparison between the different competitive levels, the statistical analysis demonstrated that, for the main performance variables of the f-v profile, players competing in the 1st national division present a more balanced FVimb (83.05 ± 20.34) than players in the 2nd national division (62.94 ± 21.28), however, they have a lower Pmax (26.95 ± 4.17 vs 31.54 ± 6.45, respectively). When comparing the different positions, the ANOVA showed that forwards present a more balanced FVimb (84.64 ± 13.46) than midfielders (58.70 ± 21.31), while the Pmax variable presents lower values (25.11 ± 3.59 vs 32.05 ± 5.57, respectively), with no differences for the remaining positions. Although there were differences for the FVimb and Pmax variables, no difference was found for the ballistic performance variable (vertical jump) in both comparisons (level or position). The results presented in this dissertation can serve as a theoretical contribution for soccer coaches and strength and conditioning coaches, not as a way of comparing levels or positions, but rather for a better understanding of the individual neuromuscular limitations of each athlete that can maximize their ballistic performance in the game, namely, the vertical jump.